The Concept of Waqf in Sharia Insurance (Analysis Study of Life Insurance Participation in Financing Customers at Bank Sumsel Babel Sharia) - Muhammad Iqbal (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2021)
The progress of the growth of the Islamic finance industry has shown significant results in recent years. Sharia insurance is one of the Islamic financial institutions whose development is quite significant following the direction of the development of Islamic banking institutions. Insurance as a sharia financial instrument that is engaged in guaranteeing community economic activities is one of the important instruments to maintain the existence of these economic activities. The substance of sharia-based insurance that can avoid the operational principles of gharar, maysir, and usury is one of the important issues in an effort to increase public interest in implementing sharia-based financial instruments. However, efforts are needed to encourage the growth of sharia insurance, one of which is by establishing cooperation with sharia banks related to guarantees in financing facilities. This is very important, considering that one of the risks of providing financing facilities to banks is the reduction or loss of the customer's ability to meet installment obligations, in other words there will be bad financing or in conventional bank terms known as bad loans. But the problem is, many understand that paying insurance premiums when you become a financing customer is an investment that can be enjoyed when the financing is paid off. Many still expect a return on premiums that have been paid at the beginning and taken at the end of the financing maturity. So this study aims to explain how the actual mechanism for financing customer to become participants in life insurance, is there really a concept of waqf inherent in the management of premium funds paid by customers, and what is the function of premium funds collected by insurance companies.